VR‐Based improvement of aerobics teaching quality. Issue 5 (6th March 2022) - Wu, Jing
Abstract : Currently, most of students do not pay much attention to aerobics. Affected by various factors, students' participation in aerobics learning is low and lack of interest. However, regular aerobics exercise can enhance physical fitness and improve physical and mental health. Compared with other sports, aerobics is not so boring, and the exercise effect is excellent. The introduction of virtual reality (VR) technology in aerobics teaching not only makes up for the deficiency of traditional aerobics teaching, but also brings students a great sense of novelty, and teachers' teaching efficiency and students' learning efficiency will be significantly improved. The empirical variogram‐based 360° aerobics teaching video coding unit (CU) partition algorithm is proposed to improve coding efficiency and provide real visual experience. Experiments show that the proposed algorithm performs well in BD‐Rate and Quality of Experience (QoE), so that students can adjust movements according to the standard aerobics movements, which will greatly improve the efficiency of aerobics teaching. Abstract : The QoE of the aerobics teaching algorithm proposed in this paper is always the highest with the increasing of bitrate. In contrast, the QoE of the other three baselines does not even exceed 90%. This shows that the proposed algorithm not only saves coding time, but also has a good QoE.